Notes on two rare and little-known Indo-Pacific snapping shrimps, Alpheus percyi Coutière, 1908 and A. pseudopugnax (Banner, 1953) (Decapoda, Alpheidae) - Anker, Arthur (Zootaxa, 2013)
Two uncommon, morphologically similar snapping shrimps, Alpheus percyi Coutière, 1908 and A. pseudopugnax (Banner, 1953), are reported from various localities across the Indo-West and Central Pacific. Both species are re-diagnosed based on type specimens and recently collected material; a lectotype is designated for A. percyi. The range of A. pseudopugnax, previously known only from the type locality in Hawaii, is extended considerably to French Polynesia and Reunion Island in the western Indian Ocean. Both A. percyi and A. pseudopugnax present a significant variation in the post-rostral region of the carapace, making identification of specimens based solely on morphology rather difficult. In the field, however, the two species can be easily separated by their diagnostic and very striking colour patterns. Colour patterns also suggest that A. percyi may be more closely related to the species of the A. gracilipes Stimpson, 1860 complex than to A. pseudopugnax.